Intensywność organizacji produkcji a produktywność ziemi i pracy w rolniczych spółdzielniach produkcyjnych w Polsce - Gołaś, Zbigniew; Wysocki, Feliks (Wydział Prawa i Administracji UAM, 1989)
The article presents diversifications in intensity of organization of production in the cooperative sector of Polish agriculture and connections between the level of organization and productive force resources on one hand and the efficiency of economy on the other. The research carried out on the basis of 1987 data indicates that the organization of production in agricultural cooperatives is low, mostly in consequence of insufficient density of livestock. Besides, there exists a relation between the level of intensity of organization on one hand and natural conditions together with the resources of production factors on the other. The analysis of regression showed that a main role in shaping the efficiency of agricultural production in a cooperative, measured by productivity of land labour, is played by the intensity of production expressed in terms of material outlay value. To a lesser degree productivity was influenced by natural conditions and the level of employment. Besides, the intensity of organization is to a considerable extent shaped by price relations between agricultural produce and means of production. In consequence, it leads to giving up the agricultural production in favour of undertaking more profitable activity in non-agricultural sectors.
Intensity of organization and efficiency of economic activity in agricultural production cooperatives in Poland